Development of Cerebral Microbleeds in the APP23-Transgenic Mouse Model of Cerebral Amyloid Angiopathy—A 9.4 Tesla MRI Study - Reuter, Björn; Venus, Alexander; Heiler, Patrick; Schad, Lothar; Ebert, Anne; Hennerici, Michael G.; Grudzenski, Saskia; Fatar, Marc (Frontiers in Aging Neuroscience, 2016)
Background: Cerebral amyloid angiopathy (CAA) is characterized by extracellular deposition of amyloid β (Aß) around cerebral arteries and capillaries and leads to an increased risk for vascular dementia, spontaneous lobar hemorrhage, convexal subarachnoid hemorrhage, and transient focal neurological episodes, which might be an indicator of imminent spontaneous intracerebral hemorrhage. In CAA cerebral microbleeds (cMBs) with a cortical/juxtacortical distribution are frequently observed in standard magnetic resonance imaging (MRI). In vivo MRI of transgenic mouse models of CAA may serve as a useful tool to investigate translational aspects of the disease. Material and Methods: APP23-transgenic mice demonstrate cerebrovascular Aß deposition with subsequent neuropathological changes characteristic for CAA. We performed a 9.4 Tesla high field MRI study using T2, T2* and time of flight–MRA (TOF-MRA) sequences in APP23-transgenic mice and wildtype littermates at the age of 8, 12, 16, 20 and 24 months, respectively. Numbers, size, and location of cMBs are reported. Results: T2* imaging demonstrated cMBs (diameter 50-300 µm) located in the neocortex and, to a lesser degree, in the thalamus. CMBs were detected at the earliest at 16 months of age. Numbers increased exponentially with age, with 2.5±2 (median ± interquartilrange) at 16 months, 15±6 at 20 months, and 31.5±17 at 24 months of age, respectively. Conclusion: We report the temporal and spatial development of cMBs in the aging APP23-transgenic mouse model which develops characteristic pathological patterns known from human CAA. We expect this mouse model to serve as a useful tool to non-invasively monitor mid- and longterm translational aspects of CAA and to investigate experimental therapeutic strategies in longitudinal studies.